Peningkatan Keterampilan Berpikir Kritis Siswa Kelas V Mi Amir Al-Jannah Tippulue dengan Media Fun Thinkers Book - Usman, Rahima; Zakaria, Zakaria; Basysyar, Andi Haura Rafiqah (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study aims ti determine the effectiveness of the Fun Thinkers Book media in improving the critical thinking skills of fifth grade study students at MI Amir Al-Jannah Tippulue. The type of research used is quantitave research using the Pre-Experimenal approach using the One-Group Pretest-Posttest Design conducted at MI Amir Al-Jannah Tippulue in class V with a total sample of 19 students. Then the approach used in this research is a pedagogical approach. Data collection tehniques using tets, obervations and documents analysis. Then do an analysis to test the hypothesis using the SPSS version 22 application. The results of this study indicate that based on the Paired Sample T-test it shows that the tcount is 12,466 with sig of 0,000. Then the tcount value is compared a significance value at the 5% significance level, the price is obtained from the t distribution list with probability (1-a) so that a ttabel of 2,10092 is obtained. This shows that the value of tcount is greater than ttabel (12,466>2,10092). When compared with a significance value of 0,000 which is less than a significance of 0.05 (0,000<0,05), the hypothensis in this study is stated that Ho= rejected and H1= accepted. Based on the results of the the calculation of the N-Gain Score which shows the averge value of students is 57.00 or 57%, it is included in the quite effective category. With a minimum N-Gain Score of 30% and a maximum of 100%. Thus the researchers stated that the Fun Thinkers Book media was quite effective in improving the critical thinking skills of fifth grade students at MI Amir Al-Jannah Tippulue.